2020
DOI: 10.1111/btp.12758
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of elephant foraging on the structure and diversity of an Afrotropical forest

Abstract: African forest elephants (Loxodonta cyclotis) are ecosystem engineers that browse and damage large quantities of vegetation during their foraging and movement. Though elephant trail networks and clearings are conspicuous features of many African forests, the consequences of elephant foraging for forest structure and diversity are poorly documented. In this study in northeastern Gabon, we compare stem size, stem density, proportional damage, species diversity, and species relative abundance of seedlings and sap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Although forest elephants feed on hundreds of tree and liana species, a relatively low number of them constitute the majority of their diet (Merz 1981, Blake 2002). By browsing on small trees and debarking larger ones, forest elephants shape landscapes (Rosin et al 2020), both in the interior and at the edge of forests (Cardoso et al 2019). For instance, a study conducted in Mount Cameroon showed reduced tree diversity and shorter trees, but with larger diameter at breast height, in areas disturbed by forest elephants (Maicher et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although forest elephants feed on hundreds of tree and liana species, a relatively low number of them constitute the majority of their diet (Merz 1981, Blake 2002). By browsing on small trees and debarking larger ones, forest elephants shape landscapes (Rosin et al 2020), both in the interior and at the edge of forests (Cardoso et al 2019). For instance, a study conducted in Mount Cameroon showed reduced tree diversity and shorter trees, but with larger diameter at breast height, in areas disturbed by forest elephants (Maicher et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Although forest elephants help the regeneration of many tree species, their feeding behaviour and large size also cause serious damage to the vegetation. They trample seedlings (Short 1981, Piiroinen et al 2017, Rosin et al 2020), snap saplings (Omeja et al 2014, Terborgh et al 2015), break branches (Wing & Buss 1970), uproot trees, and strip their bark (Wing & Buss 1970, Blake 2002). Besides fruits and grass, terminal twigs, leaves, and bark are dominant in the forest elephant's diet.…”
Section: Resultsmentioning
confidence: 99%
“…A relatively abundant population of forest elephants thrive in Mount Cameroon forest and their impact on vegetation structure is clear. Forest sites regularly visited by elephants are subjected to disturbance (Amahowé et al, 2012; Rosin et al, 2020) and are characterised by a dense herbaceous understorey (Carroll, 1988). This also explains the character of the vertical profile, with high vegetation cover in the understorey, gradually decreasing towards the canopy.…”
Section: Discussionmentioning
confidence: 99%
“…These well‐used trails likely incur heavier and more consistent damage to vegetation, which may offset elephant seed dispersal. While studies have attempted to determine the effects of elephants on forest structure and composition (i.e., Rosin et al, 2020), it is difficult to separate elephants’ impacts from one another and from other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, elephants are prolific seed dispersers, with areas of high elephant activity usually showing greater seed deposition (Campos‐Arceiz & Blake, 2011; Powell, 1997). Dispersal by elephants is also known to improve the germination and recruitment of seeds (Chapman et al, 1992), though seedlings near elephant fruit trees are more likely to be damaged by elephants which may impact their survival (Rosin et al, 2020). Given that trails can be several decades old (Agnew, 1966), seed dispersal by elephants and other species likely leads to some of the aggregation of trees around trails.…”
Section: Discussionmentioning
confidence: 99%